2015
DOI: 10.1111/jicd.12156
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease in a remote Asian population: association between clinical and microbiological parameters

Abstract: Age, betel chewing, and a new bacterial complex other than the "red complex" correlated to periodontal breakdown in this remote adult Asian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The results of this study showed the predominance of anaerobic bacteria in the interproximal dental plaque and confirmed earlier studies in this population [1719]. Individuals with poor oral hygiene and long-standing gingivitis have the opportunity to develop a dysbiotic microbiota both supra- and subgingivally, with a lower portion of streptococci, but a higher load of anaerobic bacteria, such as P. tannerae, F. alocis, F. nucleatum , and other Campylobacter species [18,19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study showed the predominance of anaerobic bacteria in the interproximal dental plaque and confirmed earlier studies in this population [1719]. Individuals with poor oral hygiene and long-standing gingivitis have the opportunity to develop a dysbiotic microbiota both supra- and subgingivally, with a lower portion of streptococci, but a higher load of anaerobic bacteria, such as P. tannerae, F. alocis, F. nucleatum , and other Campylobacter species [18,19].…”
Section: Discussionsupporting
confidence: 92%
“…The examination included registration of dental status (number of remaining teeth), plaque index (PI), decayed, filled teeth (DFT), bleeding on probing (BoP), probing pocket depth (PPD), clinical attachment level (CAL), and calculus according to methods and criteria used in previous studies [1720]. The participants were divided into three groups according to their periodontal status; gingivitis (with PPD ≤4 mm), mild periodontitis (at least one pocket with PPD >4 mm but <7 mm), and severe periodontitis (at least one pocket with PPD ≥7 mm or suspected loss of teeth due to periodontitis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
“…These studies indicate that the prevalence and severity of periodontal breakdown populations in different countries is similar [Löe et al, 1986;Baelum et al, 1988Baelum et al, , 1996Baelum et al, , 1997aBaelum et al, , 2003Pilot, 1998;Timmerman et al, 2000;Kvarnvik et al, 2016]. In population-based studies, there appears to be little or no association between the amount of plaque and calculus and the severity of periodontal breakdown exhibited.…”
Section: Periodontal Diseasementioning
confidence: 97%